Kisah-kisah Kejujuran Pembangun Karakter Anak / Ali Muakhir ; Penerjemah, Noviana Abdu, Ary Nilandari ; Editor, Rani Yulianty. - Ali Muakhir; Noviana Abdu; Ary Nilandari; Rani Yulianty (Multi Publishing, 2013)
v, 137 hlm. : ilus. ; 19,5 cm.